IMPROVING PROJECT PORTFOLIO MANAGEMENT WITH STRATEGIC ALIGNMENT - Iamratanakul, Suparchart; Shankar, Ravi; Milosevic, Dragan (Jurnal Pendidikan Akuntansi Indonesia, 2008)
We focus this paper on a tool to improve project portfolio management. More precisely,of the three major goals that Cooper et al. specify for project portfolio management –selecting the MVP projects, balancing portfolio, and aligning project portfolio withstrategy- goal three attracted our attention. Even more precisely, we look to use strategicfit for the goal three. For this reason, we tailor our study to these three goals and showhow to achieve these goals with our analytical procedures. Finally, we conclude thispaper with results that come from testing with those procedures.